2000
DOI: 10.1176/appi.ajp.157.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Somatization in an Immigrant Population in Israel: A Community Survey of Prevalence, Risk Factors, and Help-Seeking Behavior

Abstract: Somatization is a prevalent problem among individuals in cross-cultural transition and is associated with psychological distress; demographic characteristics such as gender, age, marital status, and duration of immigration; self-reported health problems; and immigrants' help-seeking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 39 publications
7
84
1
5
Order By: Relevance
“…This study resonates in many ways with the prior findings of psychosocial and psychiatric studies among Russian immigrants in Israel (Ritsner et al, 2000(Ritsner et al, , 2001Zilber & Lerner, 1996) and in the US (Aroian, Norris, Patsdaughter, & Tran, 1998;Aroian et al, 2003), which have typically found higher rates of mental disturbances (such as depression and somatization) among women than among men. Although this study did not measure specific mental health problems, but rather general well-being and everyday functioning, its results suggest that the actual picture is more complex.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study resonates in many ways with the prior findings of psychosocial and psychiatric studies among Russian immigrants in Israel (Ritsner et al, 2000(Ritsner et al, , 2001Zilber & Lerner, 1996) and in the US (Aroian, Norris, Patsdaughter, & Tran, 1998;Aroian et al, 2003), which have typically found higher rates of mental disturbances (such as depression and somatization) among women than among men. Although this study did not measure specific mental health problems, but rather general well-being and everyday functioning, its results suggest that the actual picture is more complex.…”
Section: Discussionsupporting
confidence: 88%
“…In Israel and the US, the research on Soviet immigrants' well-being has been dominated by clinical psychologists and psychiatrists (Aroian, Norris, & Chiang, 2003;Horenczyk, 2000;Mirsky, Barash, & Goldberg, 1992;Ritsner, Ponizovsky, Kurs, & Modai, 2000;Ritsner, Ponizovsky, Nechamkin, & Modai, 2001;Zilber & Lerner, 1996), who used various standardized inventories to assess demographic differences in distress, demoralization, somatization, and other mental health outcomes, which often showed women's disadvantage. However, beyond some specific indicators of health and distress, there is paucity of less technical and broadly-framed social research on gender differentials in psychosocial adaptation process and its costs among recent immigrants.…”
mentioning
confidence: 99%
“…These symptoms have been shown among younger populations to be usually associated with no organic pathology. The SCL-12 is widely used among clinical and community populations (Katon et al, 1990;Ritsner et al, 2000). From this study, we have previously reported that SCL-12 scores have similar associations among older patients to those found among younger populations-female gender, lower social class, depressive illness and high attendance (Sheehan et al, 2003a).…”
Section: Other Variablessupporting
confidence: 64%
“…Traditionally, immigrants tend to experience lower levels of self-esteem and a higher number of stressful life events (Martínez et al, 1999;Noh & Avison, 1996;Slonim-Nevo et al, 2006), and they tend to have a loss of significant ties when they leave their countries, frequently having to rebuild their social networks (Morrison et al, 1997;Schwarzer et al, 1994;Vega et al, 1991). The immigrants are separated from people and places they are accustomed to, they must find a job, build an entire new social life, and negotiate between their old and new cultural identities (Berry, 1992;Hovey & Magan, 2002;Oh, Koeske, & Sales, 2002;Ritsner, Ponizovsky, Kurs, & Modai, 2000;Zilber, Lerner, Eidelman, & Kertes, 2001). In this sense, and borrowing from Cowen's (2000) words, social integration in the community offers a potentially important pathway to wellness, allowing immigrant population to gain access to wider community resources that might play an important role on their SWB.…”
Section: Discussionmentioning
confidence: 99%